2022
DOI: 10.1021/acsestengg.2c00254
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Fe3O4@C Conductive Additives for Magnetic Flow-Electrode Capacitive Deionization: Reconstruction of Charge Percolation Networks

Abstract: Flow-electrode capacitive deionization (FCDI) based on suspension or semisolid electrodes is a promising alternative for largescale applications, yet precise control over their transport behavior has not yet been accomplished. Here, we report a general approach for remotely manipulating the transport of the hybrid suspension electrodes composed of core−shell Fe 3 O 4 @C nanoparticles and powdered activated carbon (AC) simply by employing a magnetic field. Benefiting from the reconfiguration of the charge perco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Figure S5b showed the survey of the samples, which showed a similar peak shape. The peaks of C 1s and O 1s were almost unchanged as seen in Figures S5c and S4d 3,19,50 The XPS results also demonstrated that AC was not oxidized. This stable operation of FCDI was attributed to the voltage drop across all components of the FCDI cell.…”
Section: Operational Stability Of the Systemmentioning
confidence: 76%
See 2 more Smart Citations
“…Figure S5b showed the survey of the samples, which showed a similar peak shape. The peaks of C 1s and O 1s were almost unchanged as seen in Figures S5c and S4d 3,19,50 The XPS results also demonstrated that AC was not oxidized. This stable operation of FCDI was attributed to the voltage drop across all components of the FCDI cell.…”
Section: Operational Stability Of the Systemmentioning
confidence: 76%
“…The increase in RE was due to the capacitive contribution of FCDI. 19 That was, when chloride ions migrate into the anode solution and were then transiently stored on the AC, a double electric layer was formed on the surface of the AC. 36 The contribution of the capacitive process was 27.48%.…”
Section: Comparison Of the Electrodialytic And Capacitive Contributio...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the electrode particles within the SS-channel appear to accumulate similarly to the RC-channel, there is a high risk for the stability of the FCDI system in long-term operation due to the narrow nature of the flow channel, such as channel blocking and slurry leakage. Except for the bend, the high-velocity shear flow generated by the single-track channel can weaken the hydrodynamic boundary layer on the surface of the straight channel, which is detrimental to charge percolation networks and electron conduction . Importantly, the HH-FCDI exhibited superior stability in desalination performance compared to RC-FCDI and SS-FCDI systems (Figure f), both C / C 0 were always steady during the continued operation, and the SR, CE, and ENRS ended up at 64.89%, 96.06%, and 5.76 μmol J –1 , respectively (Table S7).…”
Section: Resultsmentioning
confidence: 99%
“…Except for the bend, the high-velocity shear flow generated by the single-track channel can weaken the hydrodynamic boundary layer on the surface of the straight channel, which is detrimental to charge percolation networks and electron conduction. 53 Importantly, the HH-FCDI exhibited superior stability in desalination performance compared to RC-FCDI and SS-FCDI systems (Figure 7f), both C/C 0 were always steady during the continued operation, and the SR, CE, and ENRS ended up at 64.89%, 96.06%, and 5.76 μmol J −1 , respectively (Table S7). The average ASRR (2.05 μmol cm −2 min −1 ) in the whole operation of the HH-FCDI system was significantly faster than the FCDI system with a conventional flow channel (Figure 7g).…”
Section: Effect Of Different Cellmentioning
confidence: 98%